Faktor yang Mempengaruhi Tingkat Likuiditas Studi pada Perusahaan Pertambangan Batubara Di Bursa Efek Indonesia - Muhammad Basri (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
Based on research conducted on coal mining companies listed on the Indonesia Stock Exchange for the 2015-2019 period, it can be concluded that operating activity cash flow partially has a significant effect on the Current Ratio. Based on research conducted on coal mining companies listed on the Indonesia Stock Exchange for the 2015-2019 period, it can be concluded that the Net Profit Margin partially has no significant effect on the Current Ratio. Based on research conducted on coal mining companies listed on the Indonesia Stock Exchange for the 2015-2019 period, it can be concluded that Operating Activity Cash Flow and Net Profit Margin simultaneously have a significant effect on the Current Ratio. The value of Adjusted R Square (R2) or the coefficient of determination is 0.487. This figure identifies that the current ratio (variable dividends) can be explained by operating cash flow and net profit margin of 48.7%, while the remaining 51.3% is explained by other reasons not examined in this study.